118k views
2 votes
Factor: 3x4 + 9x3 -30x2

2 Answers

0 votes

Answer:

3x^2(x - 2)(x + 5).

Explanation:

3x^4 = 3 * x * x * x * x

9x^3 = 3 * 3 * x * x * x

-30x^2 = -1 * 2 * 3 * 5 * x * x

All three terms have a 3 and two x's.

3 * x * x (x * x + 3 * x - 2 * 5) = 3x^2(x^2 + 3x - 10)

x^2 + 3x - 10 = x^2 + 5x - 2x - 10 = (x - 2)(x + 5)

So, 3x^2(x - 2)(x + 5)

Hope this helps!

User Btreat
by
5.3k points
6 votes

Answer:

3x²(x - 2)(x + 5)

Explanation:

Step 1: Factor GCF

3x²(x² + 3x - 10)

Step 2: Factor Quadratic

3x²(x - 2)(x + 5)

User Dipanjan Mallick
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.